The Characteristics of the ?? Symbol Used in the DIB Mu??af and the Matter of the Necessity of This Symbol: the Example of S?rat al-Baqara - Pilgir, Muhammed (Fırat University, 2023)
The al-waqf wa al-?ibtid?? literature aims to prevent the mistakes and falsifications that the al-waqf wa al-?ibtid?? mistakes will cause in the meaning of the Qur??n. As a matter of fact, the early scholars on waqf, which has an important place in the til?wa of the Qur??n, were also meticulous and did not consider it appropriate to give qir???t ij?za before learning the places where al-waqf wa al-?ibtid?? could be performed. Based on this, it can be said that the practice of al-waqf wa al-?ibtid?? in the til?wa of the Qur??n is a meaning-centered practice that started in the period of the companions/?a??ba. Waqf errors can occur in the recitation of the Qur??n due to carelessness or ignorance. For this reason, it is important to choose the expressions that would be waqf by the q?ri? of the Qur??n correctly. For this, in addition to the necessity of good knowledge of Arabic and knowledge of Islamic sciences, it comes to the fore to gain the habit of suitable places for al-waqf-al-?ibtid??. For this reason, with the reality that the mentioned features exist in a very small part of those who read the Qur??n, the literature of al-waqf wa al-?ibtid?? has emerged, especially for those who do not have enough knowledge. The perspectives of scholars on Na?w affect the judgments they give about the places of waqf and the essence of these waqfs. As a reflection of this, there occurred significant different views and practices in the aforementioned literature. One of the issues in which there are conflicting views on this issue is the problematic of the symbol ?? and the essence of this symbol. As a matter of fact, while the mentioned symbol is not included in the Medina mu??af, which is preferred almost everywhere in the Islamic world, it is noteworthy that this symbol is preferred on almost every page in the DIB mu??af. This situation necessitated uncovering the nature and characteristic features of the ?? symbol in the DIB mu??af. In this context, depicting the problem related to the subject and determining the meaning that al-Saj?wend? attributed to the related symbol is one of the main purposes of the study. Another aim of the study is to determine the characteristic features of the symbol in question as assigned in the DIB mu??af. This study has been made on the basis of the works of al-Saj?wend?, benefiting from the information in the works of the Na?w and al-waqf wa al-?ibtid?? disciplines. Namely, the situations in which al-Saj?wend? did not consider making waqf appropriate and the examples about them were examined by comparing the information in the Na?w and al-waqf wa al-?ibtid?? works. In this study, the essence of the waqf symbol in question, and the characteristic features of this sign in the DIB mu??af have been tried to be determined in the context of S?rat al-Baqara. al-Saj?wend? applied the rules he determined on the subject to all s?rat from beginning to end, but he did not extend this symbol to all negative situations that do not comply with the rules he has determined. This is a kind of conciseness rather than a method error. In addition, it has been found that the elements that al-Saj?wend? touched on were discussed in more detail by Ibn al-Anb?r?. However, he mentioned that in many of the elements he dealt with on this subject, the meaning was not completed and the statement was incomplete. Therewithal, in very few of the examples he gave, he mentioned that they were al-waqf al-qab??. However, it has been seen that almost all of these examples do not match with the waqf places that al-Saj?wend? did not find appropriate. In the waqf system of al-Saj?wend?, the symbol ?? is used in agreement with al-waqf al-qab??, but it is not possible to say that it is a term that is completely compatible with al-waqf al-qab??. Because the places that al-Saj?wend? assigned the symbol of ??; sometimes it is in the scope of al-waqf al-qab?? and sometimes al-waqf al-al-?asan. Today's researchers, on the other hand, argue that the symbol ?? is mostly used unnecessarily in the DİB mu??af. Because Ibn al-Jazar?, who inspired this opinion, defends the idea that al-waqf al-?asan mostly takes place in places where al-Saj?wend? uses the aforementioned symbol. Again, some of today's researchers also mention that this sign is a continuation of al waqf al-murakha?. The similarities between the definitions made by al-Saj?wend? for both types of waqf led them to this idea. Considering the rules set by al-Saj?wend?, it is understood that some of the places that he does not consider suitable for waqf consist of places where the meaning is not complete. This is included in the al-waqf wa al-?ibtid?? literature as a type of al-waqf al–qab??. Another issue is that al-Saj?wend? does not find it appropriate to perform ?ibtid?? after the places that he does not find appropriate for waqf.

Vakf-ibtidâ literatürü, vakf-ibtidâ hatalarının Kur’ân’ın manasında sebep olacağı yanlış ve tahrifatın engellenmesini hedeflemektedir. Nitekim Kur’ân tilâvetinde önemli bir yere sahip olan vakf konusunda selef âlimleri de titiz davranmışlar ve vakf-ibtidânın yapılabileceği yerler öğrenilmeden kıraat icâzeti vermeyi uygun görmemişlerdir. Buna dayanarak Kur’ân tilâvetinde vakf-ibtidâ uygulamasının, sahabe döneminde başlayan anlam merkezli bir uygulama olduğu söylenebilir. Kur’ân tilâvetinde dikkatsizlik veya bilgisizlik kaynaklı vakf hataları gerçekleşebilmektedir. Bu nedenle Kur’ân okuyucusu tarafından vakf yapılacak ibarelerin doğru seçilmesi önem arz etmektedir. Bunun için iyi derecede Arapça bilgisinin ve İslâmî ilimlere vukufiyetin gerekliliği yanında, vakf-ibtidâ için uygun noktalar hakkında meleke kesbetmek hususları öne çıkmaktadır. Bu nedenledir ki bahsedilen özelliklerin Kur’ân okuyanların çok küçük bir kısmında karşılık bulduğu realitesiyle vakf-ibtidâ edebiyatı, özellikle ilimden yeterince behresi olmayanlara yönelik olarak ortaya çıkmıştır. Ulemanın nahiv konusunda sahip olduğu perspektifler; vakf noktalarında ve bu vakfların mahiyeti hakkında verdikleri hükümlere de etki etmektedir. Bunun bir yansıması olarak mezkûr edebiyatta kayda değer farklı görüş ve uygulamalar meydana gelmektedir. Bu konuda ihtilaflı görüşlerin mevcut olduğu meselelerden biri de “??” alameti ve bu alametin mahiyetine dair problematiktir. Nitekim İslâm dünyasının hemen her yerinde tercih edilen Medine mushafında söz konusu alamete yer verilmezken; DİB mushafında bu alametin neredeyse her sayfada tercih edilmesi dikkati calip bir durumdur. Bu durum, DİB mushafında “??” alametinin mahiyetinin ve karakteristik özelliklerinin ortaya konması lüzumunu doğurmuştur. Bu bağlamda konuyla alakalı sorunun resmedilmesi ve Secâvendî’nin ilgili alamete yüklediği anlamın belirlenmesi, çalışmanın temel amaçlarındandır. Çalışmanın bir diğer amacı ise DİB mushafında tayin edilen mevzubahis alametin hangi karakteristik özelliklere sahip olduğunun belirlenmesidir. Bu çalışma, nahiv ve vakf-ibtidâ disiplinlerine ait eserlerdeki bilgilerden istifade ile Secâvendî’nin eserleri temelinde yapılmıştır. Şöyle ki Secâvendî’nin vakf yapılmasını isabetli görmediği durumlar ve bunlara dair örnekler, nahiv ve vakf-ibtidâ eserlerindeki bilgilerin karşılaştırılması yoluyla incelenmiştir. Çalışmada, mevzubahis vakf alametinin mahiyeti ve bu alametin DİB mushafındaki karakteristik özellikleri Bakara sûresi çerçevesinde tespit edilmeye çalışılmıştır. Secâvendî, konuya ilişkin tayin ettiği kaideleri baştan sona bütün surelere tatbik etmiş; fakat bu alameti, belirlediği kurallara uymayan bütün olumsuz durumlara teşmil etmemiştir. Bu durum, usul hatası olmaktan öte bir tür ihtisardır. Ayrıca Secâvendî’nin konuya ilişkin değindiği hususların, İbnü’l-Enbârî tarafından daha detaylı bir şekilde ele alındığı tespit edilmiştir. Ne var ki İbnü’l-Enbârî, bu konuyla alakalı olarak ele aldığı maddelerin birçoğunda mananın tamamlanmadığını ve kelamın nakıs olduğunu zikretmiştir. Bununla beraber verdiği örneklerin çok az bir kısmında ise onların vakf-ı kabîh olduğunu zikretmiştir. Ancak bu örneklerin tamamına yakınının, Secâvendî’nin uygun görmediği vakf noktalarıyla mutabık olmadığı görülmüştür. Secâvendî’nin vakf sisteminde ise “??” alameti, vakf-ı kabîhe mutabık olarak kullanılmakla birlikte onun tamamen vakf-ı kabîhle bağdaşan bir ıstılah olduğunu söylemek mümkün değildir. Zira Secâvendînin “??” alametini tayin ettiği noktaların; bazen vakf-ı kabîhin bazen de vakf-ı hasenin şümulünde olduğu saptanmıştır. Günümüz araştırmacıları ise “??” alametinin DİB mushafında ekseri gereksiz yere kullanıldığını öne sürmektedir. Zira bu kanaate ilham olan İbnü’l-Cezerî’, Secâvendî’nin mezkûr alameti kullandığı yerlerde çoğunlukla vakf-ı hasenin gerçekleştiği fikrini savunmaktadır. Yine günümüz araştırmacılarından bazıları bu alametin, vakf-ı murahhasın bir devamı niteliğinde olduğundan da bahsetmektedirler. Bu noktada Secâvendî’nin her iki vakf türü için yapmış olduğu tanımlar arasındaki benzerlikler onları bu fikre sevk etmiştir. İbnü’l-Cezerî’ye ait bu kanaatin doğruluğunun teyit edilebilmesi için Secâvendî’nin tayin ettiği ?? alametine dair çok sayıda örneğin incelenmesi icap edebilir. Lakin bu usul, çalışmanın sınırlarını aşan bir durumdur. Secâvendî’nin belirlediği kaideler göz önüne alındığında onun vakf için uygun görmediği yerlerin bir kısmının, mananın tamamlanmadığı noktalardan oluştuğu anlaşılmaktadır. Bu da vakf-ı kabîhin bir çeşidi olarak vakf-ibtidâ literatüründe kendine yer bulmaktadır. Bir diğer husus ise Secâvendî’nin vakf için sıhhatli bulmadığı yerlerin sonrasından ibtidâ yapılmasını da doğru bulmamasıdır.
DİB Mushafında Kullanılan ?? Alametinin Karakteristik Özellikleri ve Bu Alametin Gerekliliği Hususu: Bakara Sûresi Örneği
Keywords: Religious Studies; Din Araştırmaları